Role of ionic diffusion in polymer gel mediated growth (PMG) technique for the synthesis of nanoparticulate fillers - Sonawane, Pradip S.; Biradar, Santoshkumar S.; Radhakrishnan, S.; Kulkarni, B. D. (Materials Chemistry and Physics, 2007)
Polymer mediated growth (PMG), which forms an important method for synthesis of nanoparticles, has one of the ions bound by polymer matrix while the other is allowed to diffuse and react to form desired compound. The exact role of ionic diffusion in the formation of nanoparticles has been investigated by taking specific case studies. Typically calcium carbonate, calcium phosphate and calcium sulfate have been formed in nano-size by PMG route using polyacrylamide gel. The extent of cross-linking of the polymer matrix in the formation of gel, affects the diffusivity of ions into polymer matrix and the size of particles formed. The rates of diffusion for different extents of cross-linking of polymer are estimated during the synthesis of nanoparticles using Fick's law. The inter-correlation between the particle size formation and the diffusion length has been clearly brought out in these studies. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: ionic diffusion; nanoparticulate fillers; polymeric gels

Development of nanofibrous morphology in LDPE/LLDPE/PP blends and its effect on mechanical properties of blend films - Sonawane, Pradip S.; Radhakrishnan, S.; Bhangale, J. A.; Gadhavi, A. L.; Khare, Anagha (Journal of Applied Polymer Science, 2008)
Nanofibrous morphology has been observed in ternary blends of low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and isotactic polypropylene (PP) when these were melt-extruded via slit die followed by hot stretching. The morphology was dependent on the concentration of the component polymers in ternary blend LDPE/LLDPE/PP. The films were characterized by wide angle X-ray diffraction (XRD), scanning electron microscopy (SEM), and testing of mechanical properties. The XRD patterns reveal that the P phase of PP is obtained in the as-stretched nanofibrillar composites, whose concentration decreases with the increase of LLDPE concentration. The presence of PP nanofibrils shows significant nucleation ability for crystallization of LDPE/LLDPE blend. The SEM observations of etched samples show an isotropic blend of LDPE and LLDPE reinforced with more or less randomly distributed and well-defined nanofibrils of PP, which were generated in situ. The tensile modulus and strength of LDPE/LLDPE/PP blends were significantly enhanced in the machine direction than in the transverse direction with increasing LLDPE concentration. The ultimate elongation increased with increasing LLDPE concentration, and there was a critical LLDPE concentration above which it increased considerably. There was a dramatic increase in the falling dart impact strength for films obtained by blow extrusion of these blends. These impressive mechanical properties of extruded samples can be explained on the basis of the formation of PP nanofibrils with high aspect ratio (at least 10), which imparted reinforcement to the LDPE/LLDPE blend. (C) 2007 Wiley Periodicals, Inc.
Keywords: linear low density polyethylene; low density polyethylene; mechanical properties; melt-extruded films; nanofibrous morphology; polypropylene; ternary blends